Development of a Method for Rapid Determination of Morpholine in Juices and Drugs by Gas Chromatography-Mass Spectrometry - Mengsi Cao; Pingping Zhang; Yanru Feng; Huayin Zhang; Huaijiao Zhu; Kaoqi Lian; Weijun Kang (Journal of Analytical Methods in Chemistry)
A reliable derivatization method has been developed to detect and quantify morpholine in apple juices and ibuprofen with gas chromatography-mass spectrometry. Morpholine can react with sodium nitrite under acidic condition to produce stable and volatile N-nitrosomorpholine derivative. In this experiment, various factors affecting the derivatization and extraction process were optimized, including volume and concentration of hydrochloric acid, quantity of sodium nitrite, derivatization temperature, derivatization time, extraction reagents, and extraction time. The derivative was extracted with dichloromethane and determined by gas chromatography-mass spectrometry. The linearity range of morpholine was 10–500 μg·L−1 with good correlation, and limits of detection (LOD) and limits of quantification (LOQ) were 7.3 μg·L−1 and 24.4 μg·L−1, respectively. Low, medium, and high concentrations of morpholine were added in apple juices and ibuprofen samples to evaluate standard recovery rate and relative standard deviation. The spiked recovery rate ranged from 94.3% to 109.0%, and the intraday repeatability and interday reproducibility were 2.0%–4.4% and 3.3%–7.0%, respectively. The developed method has good accuracy and precision. This quantitative method for morpholine is simple, sensitive, rapid, and low cost and can successfully be applied to analyze the residual morpholine in apple juices and drug samples.